Belarus : a perpetual borderland - Savchenko, Andrew (Brill, 2009)
The book explains Belarusa (TM)s adherence to Soviet social, political and economic institutions. Comparative historical analysis spans the period from the 16th century to the present. Discussion concentrates on development of Belarusa (TM)s national institutions in interaction with Russia and other neighbors.
Keywords: Belarus -- History.; Belarus -- Politics and government.; Belarus -- Economic conditions.; Biélorussie -- Histoire.; Biélorussie -- Politique et gouvernement.; Biélorussie -- Conditions économiques.; HISTORY.; Economic history; Politics and government; Belarus; Grenzgebiet -- Motiv; Politik; Sociale structuur.; Politieke situatie.; Economische situatie.; Wit-Rusland.; Politik.; Grenzgebiet.; Weissrussland.; Geschichte.; History